2020
DOI: 10.1002/1873-3468.13967
|View full text |Cite
|
Sign up to set email alerts
|

An inventory of lysosomal ABC transporters

Abstract: ABC transporters fulfill diverse physiological functions in different cellular localizations ranging from the plasma membrane to intracellular membranous compartments. Several ABC transporters have been spotted in the endolysosomal system, which consists of endosomes, autophagosomes, lysosomes and lysosome-related organelles. In this review we present an overview of lysosomal ABC transporters including ABCA2, ABCA3, ABCA5, ABCB6, ABCB9 and ABCD4, discussing their trafficking routes, putative substrates, potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 157 publications
(219 reference statements)
0
27
0
Order By: Relevance
“…Unlike other ABCD transporters, ABCD4 is not found in peroxisomes, but in lysosomes. It takes part in transport of cobalamin (vitamin B12) and mutations in this transporter cause inherited defects of intracellular cobalamin metabolism [ 10 ]. Low transcript levels of this gene were also associated with shorter DFS of colorectal cancer patients [ 20 ] and ABCD4 was among amplified genes in resistant cancer cell lines [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other ABCD transporters, ABCD4 is not found in peroxisomes, but in lysosomes. It takes part in transport of cobalamin (vitamin B12) and mutations in this transporter cause inherited defects of intracellular cobalamin metabolism [ 10 ]. Low transcript levels of this gene were also associated with shorter DFS of colorectal cancer patients [ 20 ] and ABCD4 was among amplified genes in resistant cancer cell lines [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Family C is mostly dedicated to multidrug resistance (MRP1-6) [ 8 , 9 ], but ABCC6, ABCC7, and ABCC8/9 are linked to serious diseases (pseudoxanthoma elasticum, cystic fibrosis, and diabetes mellitus, respectively) [ 9 ]. ABCDs are responsible for transport of fatty acids from peroxisomes to the cytoplasm [ 10 ] and ABCGs transport various products of metabolism, xenobiotics including anti-cancer drugs, bile acids, and steroids [ 11 ]. The rest of the transporters are not involved in transport, but rather act as translational inhibitors or protein synthesis regulators (ABCFs and ABCEs) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are multidomain multispanning membrane proteins that hydrolyze ATP to transport a variety of substrates (from nutrients, metabolites, vitamins, drugs, and lipids, to trace metals and small ions) across membranes. Their defects often cause disease [4]. All ABC transporters have a similar domain architecture with at least two transmembrane domains (TMDs) and two cytoplasmic nucleotide-binding domains (NBDs) [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…In the lysosomes, doxorubicin was colocalized with Pgp-EGFP, indicating that Pgp, at least in part, mediated the lysosomal sequestration of doxorubicin as recently reported for hCMEC/D3- MDR1 -EGFP cells [ 13 ] and cancer cells [ 59 ]. As described in the Introduction, cytostatic agents enter the lysosome either by passive diffusion along the pH gradient or may be actively transported across the membrane by inward-turned Pgp embedded in the lysosomal membrane [ 11 , 12 ], although the latter mechanism is debated [ 51 , 60 ]. The fate of drugs sequestered in lysosomes remains to be elucidated in more detail, but it was suggested that they either stay trapped in lysosomes, are degraded in the lysosomes, or are eliminated from the cell by drug-induced lysosomal exocytosis, preventing lysosomal damage [ 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%